2014
DOI: 10.4103/0972-6748.151690
|View full text |Cite
|
Sign up to set email alerts
|

Study of attitude of interns toward psychiatry: A survey of a tertiary level hospital in Ahmedabad

Abstract: Background:Worldwide, multiple studies demonstrate a negative attitude of interns toward psychiatry. Scenario in Gujarat state has never been looked upon. The objective of this study is to identify the situation in this region by studying the attitude of interns toward various areas of psychiatry and to study the gender differences if any.Materials and Methods:For study, all 122 interns who attended psychiatry posting for the 1st time in their internship, over a period of 8 months were approached amongst which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
(31 reference statements)
2
7
1
Order By: Relevance
“…The students even disagreed more on questions like ‘Psychiatry is so unscientific that even psychiatrists can’t agree as to what its basic applied sciences are.’ These findings were consistent across previous studies in similar items 16 28. Few studies had contradictory results 30…”
Section: Discussionsupporting
confidence: 92%
“…The students even disagreed more on questions like ‘Psychiatry is so unscientific that even psychiatrists can’t agree as to what its basic applied sciences are.’ These findings were consistent across previous studies in similar items 16 28. Few studies had contradictory results 30…”
Section: Discussionsupporting
confidence: 92%
“…And the qualitative findings showed that there were four major barriers among patients to seek care from mental health care facilities: the rejection of mental illness by patients due to fear of societal stigma, faith on magico-religious healers, lack of availability of mental health services, and poor socioeconomic conditions. A study conducted in India also revealed that factors such as lower education and females are having more of negative attitudes towards mental health care facilities [17,22]. The present study suggested that females are best weakly related to the attitudes; they are slightly more rigid with their views and have more negative attitudes.…”
Section: Discussionsupporting
confidence: 48%
“…The present study showed no statistically significant improvement in the total score of the nursing student's attitude toward psychiatric knowledge and teaching but out of 7 items only three showed significantly improvement, According to Parikh et al (24) most of the studied students believed that psychiatry has very little scientific information and they are uncertain about the importance of psychiatric curriculum, however one -third found their undergraduate psychiatric training to be of value. McLaughlin (25) Found that nursing students generally have positive attitudes toward psychiatric ill patients, and that clinical contact can cause change in student attitudes, in either a positive or negative way.…”
mentioning
confidence: 75%
“…According to the present study there is no statistically significant improvement in the total score of the nursing students attitudes toward psychiatric treatment and hospitals, however only three items showed significant improvement, Parikh et al (24) found that the students shows agreement about the importance of psychiatric treatment and they consider psychiatric hospitals are essential for the treatment of psychiatric ill patients, this finding contradict the finding of Malhi et al (26) who mentioned that nursing students view psychiatry as less scientific and having fewer clinically effective treatment. Sartorius et al (27) mentioned five misconception about psychotropic drugs that he thought to be the reason for the negative attitude toward psychiatric treatment, they are addictive, sedative, not curing, merely treating patients and ineffective in preventing relapse.…”
mentioning
confidence: 89%